Does clinical experience impact students' capacity to diagnose dentoalveolar disorders using intraoral radiography? - Eduarda Adams Hilgert; Heraldo Luis Dias da Silveira; Mariana Boessio Vizzotto; Priscila Fernanda da Silveira Tiecher; Nádia Assein Arús (Universidade Federal do Rio Grande do Sul. Faculdade de Odontologia, 2020)
Introduction: Mastery of interpretation of radiographic images is a contributing factor in correct diagnosis of conditions affecting the dentoalveolar apparatus. It is therefore essential that students' perfect these skills while studying for their degrees. Once they embark upon their professional careers outside of the university setting, it is expected that the theoretical knowledge and clinical experience accumulated during the course of their studies will have led to improved diagnostic performance. Objective: The objective of this study was to evaluate diagnoses made using intraoral radiographs by undergraduate students at a School of Dentistry in the South of Brazil, before and after their introduction to clinical practice. Materials and methods: Diagnoses made during the second (T0) and fourth (T1) years of the undergraduate course in dentistry using interproximal and periapical radiographs were analyzed. Descriptive statistics were calculated and the McNemar test was used to compare answers at T0 and T1. Results: Fifteen students answered questionnaires at both T0 and T1. The overall percentage of correct answers was 70.5% at T0 and 61.6% at T1, with a significant difference (p = 0.024). Discussion: This study highlights the need for educational strategies that improve diagnostic competence during undergraduate clinical activities, since radiographic examinations are essential in all areas of dentistry. Conclusions: Therefore, it was concluded that the rate of correct diagnosis of dentoalveolar disorders by intraoral radiography decreased significantly after the initial years of clinical training.